2016
DOI: 10.1021/acs.iecr.6b00784
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carbon Nanotubes in Improving Thermal Stability of Polymeric Fluids: Experimental and Modeling

Abstract: At harsh conditions of high pressure high temperature (HPHT), polymers undergo thermal degradation leading to serious loss in fluid rheological and filtration properties. Nanoparticles are the most promising additives proposed to address this challenge. The stability of nanofluids is perused from various facets including rheological and filtration properties, shale stability, and zeta potential. The presence of nanoparticles could amazingly reduce the filtration at high temperatures even by 95%, and it also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…Improvement in the sealing ability, reduction in mud cake permeability and wellbore stability was observed by adding nanoparticles compared to calcium carbonate as reported by Li et al (2012). Halali et al (2016) used CNT nanoparticle as an additive to drilling fluid for increasing thermal stability of polymeric fluid. The results showed reduction in filtration by 95% at high-temperature conditions and increase in stability and zeta potential of the shale.…”
Section: Introductionmentioning
confidence: 82%
“…Improvement in the sealing ability, reduction in mud cake permeability and wellbore stability was observed by adding nanoparticles compared to calcium carbonate as reported by Li et al (2012). Halali et al (2016) used CNT nanoparticle as an additive to drilling fluid for increasing thermal stability of polymeric fluid. The results showed reduction in filtration by 95% at high-temperature conditions and increase in stability and zeta potential of the shale.…”
Section: Introductionmentioning
confidence: 82%
“…Halali et al [68] studied the role of CNTs in improving the thermal stability of polymeric fluids. They stated that the optimum formulation of sample was achieved by using CNTs, surfactant and polymers all together.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Different properties of WBM can be improved using polymers. Polymers are widely utilized to control filtration, improve rheological parameters, enhance cutting transport capacity, and improve shale recovery (Halali et al 2016). PAC, xanthan gum (XGD), carboxymethyl cellulose (CMC), starch, and partially-hydrolyzed polyacrylamide (PHPA) are the most commonplace polymers in drilling industry (Thomas 1982;Plank and Gossen 1991;Oswald et al 2006;Balestrini et al 2009;Kelessidis et al 2013;Toka and Toka 2015;Villada et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PAC, xanthan gum (XGD), carboxymethyl cellulose (CMC), starch, and partially-hydrolyzed polyacrylamide (PHPA) are the most commonplace polymers in drilling industry (Thomas 1982;Plank and Gossen 1991;Oswald et al 2006;Balestrini et al 2009;Kelessidis et al 2013;Toka and Toka 2015;Villada et al 2017). One of the disadvantages of polymers is their low performance in high-temperature and high-pressure (HPHT) conditions which bring about the degradation of polymers (Halali et al 2016). Thomas (1982) showed that the thermal stabilities of starch and CMC are in the range of 200-225 °F and 275-300 °F, respectively.…”
Section: Introductionmentioning
confidence: 99%